The Role of Job Satisfaction in Mediating the Influence of Training, Work Environment, and Work Culture on the Performance of Domestic Cargo Companies - Primadi Candra Susanto; Aswanti Setyawati; Aisyah Rahmawati; Reza Fauzi Jaya Sakti; Esti Liana; Euis Saribanon; Irwan Chairuddin (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study explores the mediating role of job satisfaction in the relationship between training, work environment, and organizational culture on the performance of domestic cargo companies. The cargo logistics sector is increasingly challenged by rising competition, rapid technological changes, and shifting service demands. This research employs a qualitative approach using a systematic literature review. Secondary data were collected from reputable international journals indexed in databases such as Scopus, Springer, Elsevier, Emerald, and Web of Science. The data were analyzed using content analysis to examine the conceptual relationships among the key variables. The findings reveal that training, work environment, and organizational culture significantly affect company performance, both directly and indirectly through job satisfaction as a mediating variable. From a managerial perspective, the study highlights the need for cargo companies to implement continuous training programs, create supportive work environments, and foster positive organizational cultures to enhance employee satisfaction and achieve sustainable performance outcomes.